Research of Parameter Matching for Range- extended Electric Vehicle based on New Type of Biaxial Transmission System - Zhao Shijing; Bi Changfei (Jixie chuandong)
With the heated development of range- extended electric vehicle,a new kind of transmission with biaxial transmission is proposed,the study of parameter matching is carried out based on the national standard stipulation of dynamic and economic performance,and the parameter result is imported into MATLAB software to simulate. The simulation results show that proposed kind of transmission perfectly satisfy the national stipulation,and has a significant improvement of performance by comparing with the original vehicle transmission.